Geotechnical influence of underlying soils to pavement failure in Southwestern Part of Nigeria / Ademila Omowumi - Omowumi, Ademila (Universiti Teknologi MARA, Perak, 2018)
Roads in Nigeria are usually constructed without in-depth knowledge of the subsoil that serves as the foundation for the road elements. Road failures are often associated to poor construction materials or inadequate design without cognisance of the underlying soils. Engineering properties of ten bulk soil samples collected from the subgrade of Arigidi/Oke-Agbe highway were investigated to determine their suitability for highway pavement. Results show that all the subgrade soils below the failed locations have higher plasticity indices, which is an indication of their high swelling potential, and they are classified as A-7-6 clayey soils with high-water adsorption capability (16.1 – 22.4%) compared to subgrade soils from the stable locations. Low compacted density (1325 – 1928 Kg/m3 ), extremely poor CBR values; 8 – 31% (unsoaked) and 3 – 8% (soaked) which indicate percentage reduction in strength of the soils up to 77% on exposure to excessive moisture and the predominance of fines (> 59%) in the soils are responsible for the degree of instability. Furthermore, soft to low stiffness (49 – 131 kN/m2 ) and poor permeability of the subgrade materials underlying the pavement result to the failure characteristics witnessed. This study shows that the suitability and behaviour of subgrade soil is dependent on its engineering properties.